2021
DOI: 10.1136/bmj.n1972
|View full text |Cite
|
Sign up to set email alerts
|

Women’s wellbeing and the burden of unpaid work

Abstract: examine how gender inequities in the time allocated to unpaid work, exacerbated by covid-19, are affecting women's mental health Soraya Seedat, executive head 1 Marta Rondon, consultant in psychiatry 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 23 publications
4
88
2
3
Order By: Relevance
“…15 This can add another layer of stress to an already stressful career. 16 The extra commitments make it harder to find the time for out of hours work needed to reach leadership positions. When planning a family, a recent survey of North American surgeons found a 42% higher rate of miscarriage when compared with the rest of the population, suggesting we still need to do more to support pregnant surgeons.…”
mentioning
confidence: 99%
“…15 This can add another layer of stress to an already stressful career. 16 The extra commitments make it harder to find the time for out of hours work needed to reach leadership positions. When planning a family, a recent survey of North American surgeons found a 42% higher rate of miscarriage when compared with the rest of the population, suggesting we still need to do more to support pregnant surgeons.…”
mentioning
confidence: 99%
“…“Very effective” was used as the reference group for all comparisons. Gender was considered a relevant demographic variable based on research suggesting that women likely bear an increased burden of care during the pandemic ( Seedat and Rondon, 2021 ). This may impact female clinicians' interest or need for telehealth provision and lead to gender differences for perceived effectiveness of telehealth.…”
Section: Methodsmentioning
confidence: 99%
“…Based on this finding, a pertinent suggestion would be that policies for maximising access to necessary healthcare should be customised to distinguish between the jobless category and job holders. Recent studies have found that jobless women are exposed to an increased risk of mental health issues, and recommend well-designed policy options to cater to their needs (40,41).…”
Section: Differences Between the Characteristics Associated With Non-...mentioning
confidence: 99%